Coolies of Capitalism Assam Tea and the Making of Coolie Labour - Varma, Nitin (Work in Global and Historical Perspective, 2016)
Coolie labour was often proclaimed as a deliberate compromise straddling the regimes of the past (slave labour) and the future (free labour). In the late 1850s, the locals were replaced by labourers imported from outside the province who were designated "coolies". Qualifying this framework of transition and introduction, this study makes a case for the "production" of coolie labour in the history of the colonial-capitalist plantations in Assam.